Analisis ketidakpastian pengukuran pada mistar ingsut rentang 0-30 cm - Agus Suryawan, I Gede Putu; Komang Dwijana, I Gusti (Jurnal Energi Dan Manufaktur; Vol 1, No 1 Juni 2006, 2012)
In science of measurement, an error is defined as difference result of measurement and the real value of the measurand.Actually, this real value is never precisely identified; consequently, the error is unknowns as well. In this case, the error canonly be estimated without knowing its real quantity. If a value will be considered as an estimated error, this value should be taken as an uncertainty. Uncertainty of Vernier Calliper determined with Type A and Type B evaluation, then the combinedstandard uncertainty is determined. Vernier Calliper that calibrated with Gauge Block class 1, the maximum uncertainty is ± 3.27 µm in dimension of 12.7 mm, with 95% confidence level.
Keywords: uncertainty in Measurement, Vernier Calliper